Exploration of the Sultan Mahmud Badaruddin Jayowikramo Grand Mosque in South Sumatra: An ethnomathematics study - Lisnani Lisnani; Romiya Gustira (Jurnal Elemen, 2023)
This study aims to explain the relevance of ethnomathematics research and the two-dimensional figure shapes in the building of the Grand Mosque of Sultan Mahmud Badaruddin Jayowikramo Palembang. Sultan Mahmud Badaruddin Jayowikramo Palembang Grand Mosque is located in Palembang, Indonesia. The method used in this study was qualitative research with an ethnomathematical approach. The research subjects were the foundation's general secretary, supervising secretary, and administrative staff. Researchers used A data collection technique in multiple processes, such as observation, documentation, and interviews. The data analysis techniques used data reduction, display, and drawing inference. As a result, it was shown that each part of Sultan Mahmud Badaruddin Jayowikramo Palembang Grand Mosque has a mathematical concept of two-dimensional figures and many shapes of two-dimensional figures from the architecture of the Grand Mosque.